Single-cell transcriptomics identifies multiple pathways underlying antitumor function of TCR- and CD8αβ-engineered human CD4 + T cells - Rath, Jan A.; Bajwa, Gagan; Carreres, Benoit; Hoyer, Elisabeth; Gruber, Isabelle; Martínez-Paniagua, Melisa A.; Yu, Yi-Ru; Nouraee, Nazila; Sadeghi, Fatemeh; Wu, Mengfen; Wang, Tao; Hebeisen, Michael; et al. (Science advances, 2020)
TCR-CD8–engineered CD4 + T cells have potent antitumor activity with sustained expression of diverse transcriptional programs. Transgenic coexpression of a class I–restricted tumor antigen–specific T cell receptor (TCR) and CD8αβ (TCR8) redirects antigen specificity of CD4 + T cells. Reinforcement of biophysical properties and early TCR signaling explain how redirected CD4 + T cells recognize target cells, but the transcriptional basis for their acquired antitumor function remains elusive. We, therefore, interrogated redirected human CD4 + and CD8 + T cells by single-cell RNA sequencing and characterized them experimentally in bulk and single-cell assays and a mouse xenograft model. TCR8 expression enhanced CD8 + T cell function and preserved less differentiated CD4 + and CD8 + T cells after tumor challenge. TCR8 + CD4 + T cells were most potent by activating multiple transcriptional programs associated with enhanced antitumor function. We found sustained activation of cytotoxicity, costimulation, oxidative phosphorylation– and proliferation-related genes, and simultaneously reduced differentiation and exhaustion. Our study identifies molecular features of TCR8 expression that can guide the development of enhanced immunotherapies.